Team mindfulness and its antecedents - Chatterjee, A.; Bruce, K.; Thakur, M. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
Studies show that the collective mindfulness of organizational members has crucial implications for organizations. However, extant research on collective mindfulness is focused at the organizational level as a whole; the subject of mindfulness of organizational sub-units such as groups and teams has remained largely ignored. Recognizing the significance of teams in today’s organizations, our paper explores four antecedents of team mindfulness: intra-team competition, constraints experienced by the team, connectedness of team members with other team’s members, and the team leader’s individual mindfulness. By exploring team mindfulness and its antecedents we contribute to a richer understanding of collective mindfulness in organizations. Our study can have direct implications for improving team mindfulness, which, in turn, can significantly serve organizational interests.
Keywords: Team mindfulness, antecedents